Fine regulation of sigma phase achieves excellent mechanical properties in Co-free CrFeNiSi0.2 medium entropy alloy - T.X. Bai; Z.Z. Mao; T.F. Cao; B.H. lin; Q.J. Zha; T.W. Zhang; H. Chang; S.G. Ma; S.Y. Du; Z.H. Wang (Journal of Materials Research and Technology)
The balance between strength and plasticity is the ultimate objective in the exploration of alloy design. This study focuses on achieving synergy between strength and toughness in the CrFeNiSi0.2 medium entropy alloy through various heat treatments to regulate the size and morphology of the σ phase. The results demonstrate that trace amounts of the σ phase began to appear after annealing at 800 °C. The volume fraction of the σ phase in the alloy and the size of the phase gradually increased as the temperature rose from 800 °C to 900 °C. Specifically, the alloy exhibits an exceptional synergy between strength and plasticity after annealing at 900 °C for 1 h, maintaining a plasticity of 18.6 %, with a yield strength of 630 MPa and keep an ultimate tensile strength exceeding 1 GPa. Subsequently, a short-term partial solution treatment was employed to eliminate the lath-shaped precipitates within the grains, further optimizing the volume fractions and morphologies of the σ phase, leading to superior mechanical properties. The plasticity increased to 21.1 %, the yield strength rose to 722.3 MPa, and the ultimate tensile strength achieved to 1133.2 MPa, with the strain-energy density reaching up to 195.76 mJ/mm3. The σ phase is vital for high strain-energy density in the researched alloys, as it refines grains, enhances the strain gradient effect, and coordinates deformation. This finding paves the way for the further development of higher performance Si-added Co-free medium/high entropy alloy.